Incorporation of phosphorus oxyacids into layered double hydroxides - Williams, G; Rees, N; O'Hare, D (2009)
Four phosphonate anions (methyl-, ethyl-, phenyl- and benzylphosphonate) were successfully incorporated into [Cu2Cr(OH)6]Cl·yH2O. It was found that two phases exist for the phenylphosphonate intercalate; one in which the anions are arranged perpendicular to the layers, and one with a tilted orientation. Systematic variation of the reaction conditions allowed the former to be isolated with phase purity, but not the latter. The solid-state 31P NMR data suggest that proton transfer may occur between host and guest. Some neutral guest is incorporated in the case of phenylphosphonate and benzylphosphonate, presumably owing to relatively poor solvation of these guests. Heat treatments only resulted in the formation of a covalent bond between host and guest in the case of the methylphosphonate intercalate. The intercalation of the related and redox-active phenylphosphinate into a range of LDHs is also reported. Time-resolved in situ diffraction techniques were used to both monitor and quantify the intercalation of phenylphosphonate into [Cu2Cr(OH)6]Cl·yH2O and phenylphosphinate into the hexagonal form of [LiAl2(OH)6]Cl·yH2O. Kinetic and mechanistic parameters have been determined from the diffraction data. © 2009 Elsevier Masson SAS. All rights reserved.